2012
DOI: 10.1002/spe.2161
|View full text |Cite
|
Sign up to set email alerts
|

A holistic approach to model‐based testing of Web service compositions

Abstract: The behavior of composed Web services depends on the results of the invoked services; unexpected behavior of one of the invoked services can threat the correct execution of an entire composition. This paper proposes an event-based approach to black-box testing of Web service compositions based on event sequence graphs, which are extended by facilities to deal not only with service behavior under regular circumstances (i.e., where cooperating services are working as expected) but also with their behavior in und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
1
48
0
Order By: Relevance
“…Tools were developed to support the main steps of MBT, such as modeling, test generation, concretization, and test execution. The chapter is a summary of results published in (Belli et al, 2013).…”
Section: Summary Of Contributions and Dissertation Outlinementioning
confidence: 99%
See 3 more Smart Citations
“…Tools were developed to support the main steps of MBT, such as modeling, test generation, concretization, and test execution. The chapter is a summary of results published in (Belli et al, 2013).…”
Section: Summary Of Contributions and Dissertation Outlinementioning
confidence: 99%
“…Faults were detected not only in the SUT, but also in the specification of a non-trivial service-oriented application. The case study was reported in (Belli et al, 2013).…”
Section: Summary Of Contributions and Dissertation Outlinementioning
confidence: 99%
See 2 more Smart Citations
“…Diaz et al [5] proposed a method to generate correct WS-BPEL skeleton documents from WS-CDL documents by using the Timed Automata as an intermediary model in order to check the correctness of the generated Web Services with model checking techniques. Belli F et al [10] proposed a new model to verify the correctness of web service compositions. It can be seen that model checking technology is widely used and gives qualitative results in the form of "yes" or "no".…”
Section: Introductionmentioning
confidence: 99%